2015
DOI: 10.1007/s10653-015-9683-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in antioxidant defense system of workers chronically exposed to arsenic, cadmium and mercury from coal flying ash

Abstract: Humans are exposed to different stress factors that are responsible for over-production of reactive oxygen species. Exposure to heavy metals is one of these factors. The aim of the study was to analyze the effect of chronic exposure to heavy metals through coal flying ash on the efficiency of antioxidative defensive mechanisms, represented by the activity of superoxide dismutase, glutathione peroxidase and ascorbic acid. Nonessential elements such as arsenic and mercury levels showed a significant increase (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Most researchers have conducted studies in workers exposed to fly ash. Occupational researchers report relationships between exposure to fly ash and increased arsenic and mercury levels in exposed workers (Zeneli, Sekovanic, Ajvazi, Kurti, & Daci, ), increased oxidative stress (Zeneli et al, ), increased frequencies of chromosomal aberrations (Bauman, & Horvat, ; Leonard, Deknudt, Leonard, & Decat, ), respiratory effects (Cho, Cho, Shrivastava, & Kapre, ), and earlier mortality from cancer (Bencko, Rames, Fabianova, Pesek & Jakubis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have conducted studies in workers exposed to fly ash. Occupational researchers report relationships between exposure to fly ash and increased arsenic and mercury levels in exposed workers (Zeneli, Sekovanic, Ajvazi, Kurti, & Daci, ), increased oxidative stress (Zeneli et al, ), increased frequencies of chromosomal aberrations (Bauman, & Horvat, ; Leonard, Deknudt, Leonard, & Decat, ), respiratory effects (Cho, Cho, Shrivastava, & Kapre, ), and earlier mortality from cancer (Bencko, Rames, Fabianova, Pesek & Jakubis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational studies have found that power plant workers who were exposed to fly ash had significantly higher blood levels of arsenic and mercury compared to healthy controls (Zeneli, Sekovanic, Ajvazi, Kurti, & Daci, 2016).…”
Section: Coal Ash and Human Healthmentioning
confidence: 99%
“…It has been demonstrated that coal fly ash is a very real exposure for those who work in jobs where coal combustion occurs (21). A study published in 2015 by Zeneli et al.…”
Section: Fly Ash and Potential Health Problemsmentioning
confidence: 99%
“…A study published in 2015 by Zeneli et al. examined the relationship between fly ash and how it affected the antioxidant defense systems of power plant works in Kosovo (21). A total of 97 adult male participants were selected, 70 were power plant workers and 27 were healthy inhabitants of the Dragash rural municipality, a location considered to be relatively free of air pollution.…”
Section: Fly Ash and Potential Health Problemsmentioning
confidence: 99%